The coronavirus disease 2019 infodemic: a concept analysis - Choi, Sujin (Frontiers in Public Health, 2024)
Aim: This study aimed to analyse the coronavirus disease-19 (COVID-19) infodemic phenomenon in the medical field, providing essential data to help healthcare professionals understand it. Methods: This study utilised a hybrid model for concept analysis. In the theoretical phase (first phase), a literature review was conducted using ScienceDirect, PubMed, CINAHL, ProQuest, Scopus, Web of Science, DBpia, RISS, and KISS. Semi-structured interviews, involving eight physicians and six nurses, were used in the fieldwork phase (second phase). In the final analytical phase (third phase), the results of the preceding phases were combined. Results: Based on the findings of these phases, the COVID-19 infodemic can be defined as 'the phenomenon of information flood, reproduction, dissemination, and asymmetry, which occurred during the pandemic through social networks among the public lacking essential knowledge of infectious disease, and is associated with negative and positive effects.' Conclusion: Our findings can help the Ministry of Health and Welfare and healthcare professionals to understand the phenomenon of the infodemic and prepare necessary strategies and education programs for the public. Therefore, the provision of basic data is important for developing influential roles for healthcare professionals during infectious disease outbreaks.